Socio-Economic Capital Conditions of Communities Living in Slum Settlements: A Case of Surabaya - Putri, Shinta Permana; Syaluca, Katrina Alyssa (Jurnal Pendidikan Sosiologi dan Humaniora, 2026)
This study was driven by the need to understand the multidimensional vulnerability of urban slum communities, which involves not only housing conditions but also the social and economic capacities of residents. Morokrembangan Subdistrict in Surabaya was selected as the study area because it represents a densely populated slum located in a coastal–industrial zone with significant environmental pressure. The research applied a qualitative approach using primary data collected through in-depth interviews with community leaders and residents, field observations of environmental conditions, and visual documentation. Data were analyzed using content analysis based on social, economic, and physical environmental capital variables. The findings show a simple pattern: community organization is active, but trust among residents and confidence in social assistance systems are low. Economically, most households can meet basic needs but remain highly vulnerable due to unstable informal jobs and limited access to capital. Physically, housing and infrastructure conditions are still inadequate, although clean water access and environmental awareness are relatively good. These results highlight clear policy implications. Social assistance programs should use vulnerability-based criteria rather than relying mainly on housing appearance. Local governments need to expand access to microfinance and community economic empowerment to reduce dependence on insecure informal work. At the same time, upgrading basic infrastructure especially housing quality, drainage, and neighborhood roads should be prioritized. Strengthening participatory and transparent governance is also essential to rebuild public trust and improve the effectiveness of development programs in slum areas.